Photoelectrochemical biosensor based on SiW12@CdS quantum dots for the highly sensitive detection of HPV 16 DNA - Cheng, Yao; Sun, Chaoyue; Chang, Yuhua; Wu, Jiayin; Zhang, Zhihao; Liu, Yunqing; Ge, Shenguang; Li, Zhao; Li, Xiao; Sun, Liang; Zang, Dejin (Frontiers in Bioengineering and Biotechnology, 2023)
A highly sensitive biosensor for detection of HPV 16 DNA was constructed based on Keggin type polyoxometalate (SiW12) grafted CdS quantum dots (SiW12@CdS QDs) and colloidal gold (Au NPs) which represented remarkable selectivity and sensitivity upon target DNA detection owning to its excellent photoelectrochemical (PEC) response. Herein, an enhanced photoelectronic response ability was achieved with the strong association of SiW12@CdS QDs by the Polyoxometalates (POMs) modification which was developed through convenient hydrothermal process. Furthermore, on the Au NPs modified ITO slides, multiple sites tripodal DNA walker sensing platform coupled with T7 exonuclease was successfully fabricated with SiW12@CdS QDs/NP DNA as probe for detecting HPV 16 DNA. Due to the surface plasmon resonance effect (PLSR) of Au NPs, the photosensitivity of the as-prepared biosensor was further improved under I- 3/I- solution and avoided the use of other toxic regents to living organisms. Finally, under optimized conditions, this as-prepared biosensor protocol demonstrated wide linear ranges (15-130 nM), LOD of 0.8 nM, with high selectivity, stability, and reproducibility. Moreover, the proposed PEC biosensor platform offers a reliable pathway for detecting other biological molecules with Nano-functional materials.